Ghosted by Government - Amy Kristin Sanders (Brechner Center for Freedom of Information, University of Florida, 2021)
Public records laws across the United States operate under the presumption that citizens should have access to government records, but obtaining this information is not always a simple undertaking. Although state public records laws vary, only a few establish a requirement that government entities acknowledge the existence of a request. And while some state laws mandate a time limit within which entities are supposed to produce records or issue a denial, those limits vary considerably from the specific three business days to the vague requirement of promptness. We analyzed these requirements in the 50 states and recommend policy changes that would hold government entities accountable to requestors and create a more level playing field for citizens seeking public records that should presumptively be open.